Morphogenesis - D.R. Khanna; Morphogenesis (Firm); Images Publishing (New Delhi. Discovery publishing house, 2004)
This highly anticipated new monograph delves into an exciting selection of esteemed works by Delhi-based firm Morphogenesis, one of the most productive and creative architectural firms in India and a world-leader in zero net energy and sustainable design. This richly illustrated book combines stunning imagery with a comprehensive study outlining the firm's strong philosophical design intent across a vast range of typologies: residential; institutional; commercial; hospitality; offices; houses; interiors; public and master planning. Morphogenesis reinterprets India's architectural roots and consistently employs passive environmental solutions for a unique, contextual contemporary language. The Morphogenesis journey is a reflection of the contemporary Indian perspective within the global context, incorporating its inspired, forward-thinking vision while respectfully referencing the spirit of traditional Indian subcontinental architecture, and all the while maintaining an intimate focus on the environmental context and culture of the project.
Morphogenesis, Delhi-based architectural firm founded by Manit Rastogi and Sonali Rastogi.
Includes bibliographical references (pages 211-212) and index.
Keywords: Morphogenesis